Molecular Characterization of Cryptosporidium spp. in Brandt's Vole in China - Feng, Shengyong; Chang, Han; Wang, Ye; Huang, Chengmei; Han, Shuyi; He, Hongxuan (Frontiers in Veterinary Science, 2020)
Cryptosporidium spp. are important intestinal parasites that infect humans and various animals, including wildlife. Currently, few epidemiological data in wild rodents, especially in voles, are available. In the present study, a total of 678 Brandt's vole feces samples were collected from Maodeng Livestock Farm and East Ujimqin, Inner Mongolia. The overall prevalence of Cryptosporidium spp. was 18.7%. Significant differences were not found between genders but between locations and weight groups. Moreover, three known species/genotypes, C. suis, Cryptosporidium environmental sequence and Cryptosporidium muskrat genotype II, and a novel Cryptosporidium species/genotypes of Brandt's vole was identified. To the best of our knowledge, this is the first report of Cryptosporidium spp. infection in Brandt's vole worldwide. These findings imply Brandt's voles might be a potential source of human cryptosporidiosis.